Pengaruh Pemberian Motivasi terhadap Hasil Belajar Peserta Dewasa di Bimbel Al Khoiriyah - Atyasuraya, Fariatul; Fadilah, Aginta; Andora, Adel (EL-EMIR Institute, 2025)
This This study aims to analyze the effect of motivation on the learning outcomes of adult learners at Bimbel Al Khoiriyah. The background of this research stems from the low learning enthusiasm often found among adult learners, which is influenced by factors such as fatigue after work, lack of internal drive, and limited motivational support in the learning environment. In adult education, motivation plays a crucial role in determining learning success, as adults possess different learning needs and characteristics compared to younger students. This research employed a quantitative approach with a simple experimental method. The treatment involved motivational sessions delivered through brief lectures and inspirational messages before the learning activities began. The study involved six adult participants enrolled in the tutoring program. Data were collected using pre-test and post-test assessments to measure learning achievement. The results showed an increase in the average score from 70 to 85 after the motivational treatment, indicating a positive influence of motivation on learning outcomes. The findings highlight the importance of motivation in improving both the process and outcomes of learning, especially among adult learners who face unique challenges in balancing education and daily responsibilities. With appropriate motivational strategies, adult learners can become more focused, confident, and capable of achieving better academic performance.